VALIDASI METODE SPEKTROFOTOMETRI UV-VIS PADA PENETAPAN KADAR BORAKS DI DALAM BAKSO - Karolina Rosmiati; Miryam Feby Br Sitinjak; Ignatius Yulianto Wibowo (Bajang Institute, 2025)
Method validation is an essential element used to demonstrate that laboratory examination parameters meet the requirements for their use. Method validation parameters include accuracy, precision, specificity, linearity, limit of detection (LOD), and limit of quantification (LOQ). The purpose of this study was to determine the results of the UV-Vis Spectrophotometry method validation in determining the levels of borax in meatballs. The samples used in this study were meatballs. The initial stage of the research involved optimizing the wavelength, followed by method validation, and subscquently qualitative and quantitative analysis of borax in meatballs. Optimization of the borax wavelength resulted in optimal results at 430 nm. The method validation stage yielded specificity test results from the three spectrum profiles indicating that there was no matrix influence at the selected wavelength of 430 nm; the linearity test had an R2 value of 0.9861, the accuracy test resulted in a % recovery of 93.32%, the precision test resulted in a Relative Standard Deviation (RSD) value of 2.7%, and the LOD value obtained was 2.067 ppm & LOQ 6.889 ppm. Qualitative analysis with curcumin paper showed all samples to be positive for borax, while in the quantitative determination of borax levels using UV-Vis spectrophotometry method from 8 samples, 5 samples contained borax and 3 samples did not contain borax with the highest average borax content of 158.81 ppm (sample A) and the lowest of 7.42 ppm (sample G).